Case report: Germline POT1 mutation in a patient with GIST and lung adenocarcinoma - Martino, Stefania; De Summa, Simona; Pilato, Brunella; Digennaro, Maria; Laera, Letizia; Tommasi, Stefania; Patruno, Margherita (Frontiers in Oncology, 2024)
POT1(Protection of Telomeres 1) is involved in telomere maintenance and stability, it plays a crucial role in the preservation of genomic stability. POT1is considered as a high -penetrance melanoma susceptibility gene, but the number of cancer types associated to pathogenic germline variants of POT1 is gradually increasing, including chronic lymphocytic leukemia (CLL), angiosarcomas, and gliomas, even though many associations are still elusive. Here is reported a case of a 60-year-old man, showing early onset multiple neoplasms, including: multiple melanomas, gastrointestinal stromal tumor (GIST)and lung adenocarcinoma. NGS (Next Generation Sequencing) analyses revealed a germline heterozygous pathogenic variant in the POT1 gene. Notably, GIST and lung adenocarcinoma were not previously reported in association with POT1 germline variant . Lung cancer susceptibility syndromes are very rare and actual knowledges are limited to few genes, although major genetic factors are yet unidentified. Recently, genome-wide-association-studies (GWAS) have pointed out an association between POT1 variants and lung cancer. This case report highlights the clinical relevance of POT1 alterations, particularly their potential involvement in lung cancer. It also suggests that POT1 testing may be warranted in patients with familial cancer syndromes, particularly those with a history of melanoma and other solid tumors.